A demo prototype of a reconfigurable IEEE1451.0-compliant and FPGA-based weblab - Costa, Ricardo J. (2014)
A reconfigurable weblab prototype was designed according to the I E E E1451.0 Std. based on FPG As. A brief introduction about its architecture and underlying infrastructure is presented. After an overview about the main features of the weblab, namely the standard access and the reconfiguration capability, the proposed demonstration for the exhibition session is described.